PENGUNGKAPAN DIMENSI LINGKUNGAN DAN SOSIAL MEMODERASI HUBUNGAN KINERJA KEUANGAN DAN PERSISTENSI LABA DENGAN EARNINGS RESPONSE COEFFICIENT (Studi Empiris Perusahaan Sektor Energi Tahun 2019 – 2023) - Bagus Riyanto, Muhammad Fathan; Holiawati; Ruhiyat, Endang (Jurnal Riset Terapan Akuntansi, 2025)
The purpose of this research is to examine and analyze the moderation effect of Environmental and Social Disclosure on the relationship between Financial Performance and Earnings Persistence with the Earnings Response Coefficient in Energy Sector Companies from 2019 to 2023. This study uses observational data from 145 companies, identifying a sample of 29 companies listed in the Indonesia Stock Exchange during the period. The data employed consists of secondary data in the form of financial statements and sustainability reports of the sampled companies. Hypothesis testing is conducted using a panel data linear regression model and moderating regression analysis with Eviews 12 software. The results of this research indicate that Financial Performance has an effect on the Earnings Response Coefficient. Earnings Persistence also influences the Earnings Response Coefficient. However, Environmental and Social Disclosure does not moderate the relationship between Financial Performance and the Earnings Response Coefficient. Likewise, Environmental and Social Disclosure does not moderate the relationship between Earnings Persistence and the Earnings Response Coefficient.These findings highlight that companies with consistent earnings and good transparency are more appealing, especially in the context of market uncertainty. Conversely, Environmental and Social Disclosure appears to be less relevant for short-term investment decision-making, given that investors tend to focus more on immediate financial results. Therefore, investors are advised to prioritize companies that demonstrate stable financial performance and maintain earnings, in order to enhance the potential return on investment. Keywords: Environmental and Social Disclosure, Financial Performance, Earnings Persistence, Earnings Response Coefficient.